Empowerment Model of Local Institutions in Realizing Nagari Tageh: Study in Nagari Sungai Kunyit - Indraddin, Indraddin; Retno, Anggraini (Jurnal Mamangan, 2023)
Community empowerment is important for local institutions in realizing Nagari Tageh. Tageh means it must be flexible in the fields of health, education, food, economy, socio-culture, information, disasters, bundo kanduang, security and controlling community diseases in Nagari Sungai Kunyit. This research aims to identify a model for empowering local institutions in the Nagari Tageh program in Nagari Sungai Kunyit. This research analysis tool uses community empowerment theory according to Jim Ife. The research methodology uses a qualitative approach and case studies, the techniques used are observation, in-depth interviews, documentation studies and focus group discussions (FGD). This research shows that the empowerment model does not involve the community in a participatory manner. The empowerment model is based on local institutional analysis, namely the empowerment of formal Nagari government institutions and the informal institution Kerapatan Adat Nagari (KAN) as an intermediate goal of empowering community groups . The empowerment model in realizing Nagari Tageh is the empowerment model in realizing Nagari Tageh is the local community involvement model and the media utilization model. A model of community involvement by identifying local institutions, related to the values and institutions available in the nagari, for example youth institutions, the density of nagari customs. Meanwhile, the media utilization model is to identify media activists in the nagari, both individually and institutionally, who actively use social media, and then collaborate with the nagari or tourism business actors. the local community involvement model and the mass media model. This model functions to empower formal Nagari government institutions and informal Nagari traditional institutions (KAN) as an intermediary goal for empowering community groups. Novelty in this research is a model of community empowerment based on local institutions.